Strategi Pemasaran Jasa Pendidikan dalam Upaya Meningkatkan Citra Madrasah Swasta (Studi Kasus di MTs Sudirman Jatisrono, Wonogiri) - Eka Yuni Purwanti; Ririn Nuraini (Tarbawi: Journal of Islamic Education, 2021)
This research is motivated by the fact that in this globalization era there are a lot of competitions in the world of education. The large number of public school makes private schools underestimated by the community. The competition between schools and madrasahs are increasing rapidly due to how the marketing strategies are implemented. So this research is to determine: How is the marketing strategy of educational services at MTs Sudirman Jatisrono, Wonogiri; How is the implementation of the marketing mix strategy for educational services to improve the image of MTs Sudirman Jatisrono, Wonogiri; How is the public response of the implementation of marketing mix strategy for educational service to improve the image of MTs Sudirman Jatisrono, Wonogiri.This research is qualitative research. Based on the data findings, MTs Sudirman Jatisrono, Wonogiri carried out three things which form the basis of marketing strategy. First, Segmentation (Market Segmentation); Targeting (Establishing Target Markets); Positioning (Determining Market Position). Second, there are seven elements that are very concerned by MTs Sudirman Jatisrono Wonogiri in order to achieve the expected goals namely : Product, the products provided various of intra- curricular and extra- curricular activities as well as providing good services for the users. Price, the cost offered is very affordable by all level of society. Place/ Location is located near the highway and the road is accessible. Promotion, it is carried out through various media and activities. People / Participant are professional teaching staff and based on their fields. Physical Evidence (physical facilities), providing buildings and infrastructure to distribute service. Process, this carried out with various methods and strategies. Third, a good relationship will create a good image, so the marketing mix will get a positive response from the society. Many factors are influencing the service users, both of prospective students and the society. Some are according to internal desires and external desires. From socio- cultural and psychological factors, those will be able to influence prospective service users or prospective students who will enter to MTs Sudirman Jatisrono, Wonogiri.